2018
DOI: 10.3390/app8040560
|View full text |Cite
|
Sign up to set email alerts
|

Development of ELISA-Like Fluorescence Assay for Melamine Detection Based on Magnetic Dummy Molecularly Imprinted Polymers

Abstract: We present a directly competitive fluorescence assay for highly sensitive detection of melamine in milk using magnetic dummy molecularly imprinted polymers (MDMIPs). The detection principle is based on competitive binding between the fluorescent label and melamine on the MDMIPs. The fluorescent label was obtained by combining fluorescein isothiocyanate (FITC) with melamine in ethanol and water. MDMIPs were prepared on the surface of Fe 3 O 4 @SiO 2 nanoparticles using 2,4-diamino-6-methyl-1,3,5-triazine as dum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Recent studies have shown that MIP-based sensors successfully combine the advantages of MIP receptors and various sensing platforms, and have great potential for application in food detection. MIPs devices based on their signal transduction principles include optical (Liu G. et al, 2018), electrochemical (Ai et al, 2018), and biosensing technologies (Zhang et al, 2018). The comparison of different detection methods for chemical pollutants based on MIPs-Sensor is given in Table 2.…”
Section: Mip-based Sensorsmentioning
confidence: 99%
“…Recent studies have shown that MIP-based sensors successfully combine the advantages of MIP receptors and various sensing platforms, and have great potential for application in food detection. MIPs devices based on their signal transduction principles include optical (Liu G. et al, 2018), electrochemical (Ai et al, 2018), and biosensing technologies (Zhang et al, 2018). The comparison of different detection methods for chemical pollutants based on MIPs-Sensor is given in Table 2.…”
Section: Mip-based Sensorsmentioning
confidence: 99%
“…Fluorescence sensors for melamine in milk and infant milk powder were established by detecting the fluorescence intensity of FITC-Mel in the respective solutions. The linear range is 0.1–20.0 mg/Kg and the detection limit is 0.05 mg/Kg [59].…”
Section: Construction Of a Mifsmentioning
confidence: 99%
“…In this context, several efforts have been already devoted to discovering new signal reporters to increase ELISA sensitivity [3] and to pinpoint capturing agents, i.e., mimetics [8], able to flank and/or supplant antibodies that generally are expensive and sensitive to environmental conditions. Looking at mimetic capturing agents, the literature has highlighted aptamers and molecularly imprinted polymers (MIPs) as the most promising ones to develop diagnostic "antibody-free" ELISA-like format assays, i.e., enzymelinked oligonucleotide assay (ELONA) [6,9], biomimetic enzyme-linked immunoassay (BELISA) [10][11][12][13][14][15][16][17][18][19], pseudo-ELISA [7,[20][21][22][23], or nanoparticle-based assay (MINA) [1,15,[24][25][26][27][28][29]. At present, a positive imbalance of the literature is in favor of aptamers, with only a few reports about MIPs starting from 2014.…”
Section: Introductionmentioning
confidence: 99%